Estudo do sofrimento psíquico de profissionais da saúde mental em Centro de Atenção Psicossocial, Fortaleza-CE - Cavalcante, Leônia Maria Santiago (2008)
This research was intended to unveil the types of mental suffering lived by the professional of Mental Health in a Center for Psychosocial Care (CAPS), located in Fortaleza, Ceará, from the perception of these professionals inserted in this new modality of care in Mental Health. The study has as a theoretical foundation, Psychoanalysis, more specifically the contributions of Escola Dejouriana, known as Psicodinâmica Labour. The qualitative approach was used in open structured interview. The research subjects are 09 (nine) professionals, male and female, with ages between 25 and 47 years old. The results, inapplicable to generalizations, indicated that these professionals attribute value to their work and gained social recognition through it; their tasks create physical and emotional damage, such as fatigue, stress, anxiety, impotence, anger, ambivalence, peaks hypertensive, gastritis, insomnia, somnolence, migraine tendinitis. There are social conflicts in relationship with other professionals, especially difficulties related to the development of an interdisciplinary work. The ways of confronting mental suffering includ leisure time, sports activities, contact with family and friends and defensive strategies cover the denial, projection, rationalization, identification, somatization, sublimation, passivity, improvisation and individualism.